Pertanggungjawaban Pidana Korporasi Menurut Vicarious Liability Theory - Kukuh Dwi Kurniawan; Dwi Ratna Indri Hapsari (Jurnal Hukum IUS QUIA IUSTUM, 2022)
The development of the corporation is eventually positioning itself as an entity that gets stronger and more powerful due to its advantages over entities in the form of natural humans. These advantages can be realized through a combination of a group of people and assets that they can create a social impact around them. Corporations that have been sentenced to criminal penalty in the form of monetary fine create injustice as they consist of a collection of people from various duties and their respective functions, hence only a few people have the authority to determine the direction of the corporate policy, therefore the penalty in the form of fine are distributed to all sectors of the corporation to share the burden. This shows that the corporation management is the party responsible for corporate crimes. This study uses a normative juridical method by parsing the doctrine of vicarious liability. The results of this study conclude that to identify who is most responsible for the criminal acts of the corporation through the approach of Vicarious Liability Theory, it is the actually the management, where every action of the corporations falls within the authority and the will of the management, thus it is the corporate management which becomes the party most responsible for the criminal action committed by the corporation. Key Words: Corporation; vicarious liability; criminal liability Abstrak Perkembangan korporasi makin hari memposisikan sebagai sebuah entitas yang semakin kuat dan berkuasa karena memiliki kelebihan dibandingkan entitas berupa manusia alamiah. Kelebihan itu dapat diwujudkan melalui gabungan sekumpulan manusia dan kekayaan sehingga dapat menciptakan dampak sosial di sekitarnya. Korporasi yang telah dijatuhkan pidana berupa denda memunculkan ketidakadilan, karena korporasi terdiri dari kumpulan orang dari berbagai tugas dan fungsinya masing-masing, sehingga hanya beberapa orang saja yang memiliki kewenangan dan menentukan arah kebijakan korporasi tersebut, oleh karenanya adanya putusan berupa denda itu menjadikan semua sektor pada korporasi tersebut harus ikut menanggung beban denda. Hal ini memberikan gambaran bahwa pengurus korporasi sebagai pihak yang bertanggung jawab atas tindak pidana korporasi. Penelitian ini menggunakan metode yuridis normatif dengan mengurai doktrin vicarious liability. Hasil penelitian ini menyimpulkan bahwa untuk mencari siapa yang paling bertanggung jawab atas perbuatan pidana dari korporasi melalui pendekatan Vicarious Liability Theory adalah pengurus, dimana langkah gerak korporasi merupakan kewenangan dan kehendak dari pengurus sehingga pengurus korporasi menjadi pihak yang paling bertanggungjawab atas korporasi yang melakukan perbuatan pidana. Kata Kunci: Korporasi; vicarious liability; pertanggungjawaban pidana